London’s rise as an offshore RMB financial centre: state-finance relations and selective institutional adaptation - Töpfer, Laura-Marie; Hall, Sarah (Taylor and Francis, 2018)
China’s currency, the Renminbi (RMB), is increasingly important in global financial markets, facilitated by the global expansion of offshore RMB centres. This paper examines London’s development as the first Western offshore RMB centre established in 2013, drawing on original research conducted between 2013 and 2015 in London and China. The longitudinal analysis reveals that the development of RMB finance in London is characterised by selective adaptation in which state-private bargaining dynamics have shifted from strategic alignment to a bifurcation of interests. Understanding these state-finance relations has important implications for research and policymaking concerned with (offshore) financial centres and RMB internationalisation.